PENERAPAN KEADILAN RESTORATIF DALAM PERKARA TINDAK PIDANA PENGANIAYAAN DI POLRES BANDUNG - Baruna, Muhammad Mirza; Rahmat, Diding (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2024)
The application of restorative justice in handling cases of criminal acts of abuse at the Bandung Police is a way to resolve conflicts in a more humane and reconciling manner. If used together with Article 352 of the Criminal Code and Article 351 Paragraphs (1) and (2) of the Criminal Code to resolve cases of criminal acts of abuse, then restorative justice is considered to be a very effective and efficient process in the Bandung police area. Applying restorative justice to minor offenses makes sense when considering the purpose of the law from the perspective of casuistic priority theory, which states that the application of these priorities varies depending on specific circumstances. Moreover, progressive legal philosophy supports this, emphasizing that society is on the side of the law, not the other way around. The method used in this research is a qualitative method of secondary data and primary data. Then, the data is described descriptively in order to obtain a picture that can be understood clearly and is directed towards answering the problem being studied, so that with this analysis, the activities carried out are only to ascertain the content or meaning of the legal rules. The research results show that the application of restorative justice provides benefits such as faster case resolution, reduced recidivism rates and psychological recovery for victims. Implementation in cases of criminal acts of abuse at the Bandung Police shows positive potential but requires greater support from various parties to overcome existing obstacles